Free sugar profile in cycads - Marler, Thomas E.; Lindström, Anders J. (Frontiers in Plant Science, 2014)
The sugars fructose, glucose, maltose, and sucrose were quantified in seven tissues of Zamia muricata Willd. to determine their distribution throughout various organs of a model cycad species, and in lateral structural roots of 18 cycad species to determine the variation in sugar concentration and composition among species representing every cycad genus. Taproot and lateral structural roots contained more sugars than leaf, stem, female strobilus, or coralloid roots. For example, taproot sugar concentration was 6.4-fold greater than stem sugar concentration. The dominant root sugars were glucose and fructose, and the only detected stem sugar was sucrose. Sucrose also dominated the sugar profile for leaflet and coralloid root tissue, and fructose was the dominant sugar in female strobilus tissue. Maltose was a minor constituent of taproot, leaflet, and female strobilus tissue, but absent in other tissues. The concentration of total free sugars and each of the four sugars did not differ among genera or families. Stoichiometric relationships among the sugars, such as the quotient hexoses/disaccharides, differed among organs and families. Although anecdotal reports on cycad starch have been abundant due to its historical use as human food and the voluminous medical research invested into cycad neurotoxins, this is the first report on the sugar component of the non-structural carbohydrate profile of cycads. Fructose, glucose, and sucrose are abundant in cycad tissues, with their relative abundance highly contrasting among organs. Their importance as forms of carbon storage, messengers of information, or regulators of cycad metabolism have not been determined to date.